Modified polyurethane polymer optical material as well as preparation method and application thereof
By optimizing the composition of polyurethane monomers and adopting a specific crosslinking system, the problems of insufficient performance and complex preparation methods of existing polythiocarbamate optical materials are solved, and modified polyurethane polymer optical materials with high refractive index, impact resistance and hardness are prepared, achieving performance improvement and cost reduction, and promoting the high-end application of optical materials.
Patent Information
- Application Number
- CN202411921896.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-11
AI Technical Summary
The performance of existing polythiocarbamate optical materials in actual applications has not yet met the needs of high-end optical applications. At the same time, the preparation method has high cost and complex processes, which limits its large-scale production and application.
Modified polyurethane polymer optical materials were prepared by selecting and optimizing the polyurethane monomer components, using polymer mercaptothil compounds, isocyanates, sulfur-containing epoxy compounds and acrylate quaternary cross-linking curing systems. While maintaining a high refractive index, this material has the advantages of strong impact resistance and high hardness.
It has achieved the improvement of high refractive index, impact resistance and hardness of optical materials, and is suitable for the production of high-end optical components, reducing production costs, simplifying processes, and promoting the large-scale production and application of optical materials.
Smart Images

Figure CN119591821A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer optical materials, and in particular relates to modified polyurethane polymer optical materials and applications in the field of optical components. Background Art
[0002] In today's era of rapid technological development, optical materials play a vital role in all fields. From eyeglass lenses and optical instruments in daily life to fiber optic communications and laser technology in high-tech fields, high-performance optical materials are indispensable. For example, in electronic devices such as smartphones and tablets, high-resolution displays require the use of high-quality optical materials to improve image clarity and color reproduction. In optical instruments such as camera lenses and telescopes, high-quality optical materials can improve imaging quality and observation effects. In addition, in the field of fiber optic communications, high-performance optical materials can improve the efficiency and stability of signal transmission.
[0003] As people's requirements for the performance of optical materials continue to increase, traditional optical materials have gradually exposed some shortcomings. For example, the refractive index of some materials is not high enough, which affects the imaging quality of the optical system; some materials have low hardness and are easily scratched, which reduces the service life. As a new type of optical material, polythiocarbamate optical material has many unique advantages. It has a high refractive index, which can improve the imaging clarity and brightness of the optical system. At the same time, the material also has good hardness and wear resistance, which can effectively resist external scratches and wear and extend the service life of optical components. In addition, polythiocarbamate optical materials also have good weather resistance and can maintain stable performance under different temperature, humidity and light conditions.
[0004] However, the current polythiocarbamate optical materials still have some problems in practical applications. On the one hand, their performance needs to be further improved to meet the needs of higher-end optical applications. On the other hand, the existing preparation methods may have problems such as high cost and complex process, which limit their large-scale production and application. In this context, by selecting and optimizing the monomer components of synthetic polyurethane, the performance of optical materials can be improved, including their refractive index, hardness and impact resistance.
[0005] In summary, the development of a new type of modified polyurethane polymer optical material has broad application prospects and important social value. Through continuous research and innovation, the performance of optical materials can be improved, production costs can be reduced, the development of optical material technology can be promoted, and better solutions can be provided for optical applications in various fields. Summary of the invention
[0006] In view of the above problems of the prior art, the present invention provides a modified polyurethane polymer optical material and a preparation method and application thereof, wherein the modified polyurethane composition optical material is composed of a quaternary crosslinking curing system of a polythiol thiol compound, an isocyanate, a sulfur-containing epoxy compound, and an acrylate. The modified polyurethane composition optical material prepared according to the method of the present invention has the advantages of strong impact resistance and high hardness while maintaining high refractive index optical properties, wherein the visible light transmittance is ≥89%, the refractive index is ≥1.62, and the surface hardness is ≥3H. It is suitable for making optical components with high requirements for optical and mechanical properties, such as prisms, lenses, and protective screens, and provides a wider range of material selection for the application of high-end optical components.
[0007] A modified polyurethane polymer optical material, which is polymerized from the following components:
[0008]
[0009]
[0010] As described above, the modified polyurethane polymer optical material, preferably, the isocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, diphenyl ether diisocyanate, triphenylmethane triisocyanate, cyclohexane diisocyanate, 4,4'-diisocyanate dicyclohexylmethane, diethylene diisocyanate, tetramethylene diisocyanate, xylene diisocyanate, tetramethyl meta-xylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dithiodipropyl diisocyanate, dithiodiethyl diisocyanate, trimethylhexamethylene diisocyanate, thiodihexyl diisocyanate, thiodipropyl diisocyanate, lysine triisocyanate, o-tolidine diisocyanate and meta-xylene diisocyanate.
[0011] In the modified polyurethane polymer optical material as described above, preferably, the polythiol thiol is a compound containing 3 or more thiol functional groups.
[0012] The modified polyurethane polymer optical material as described above, preferably, the polythiothiol mercaptan is selected from: methanetrithiol, 1,2,3-trimercaptopropane, 1,1,1-tris(mercaptomethyl)propane, dimercaptomethyl-1,4-thiacyclohexane, 2-(2,2-bis(mercaptomethylthio)ethyl)-1,3-dithiacyclohexane, 4,6-bis(mercaptomethylthio)1,3-dithiacyclohexane, 4-mercaptomethyl-1,8-dimercapto-3,6 - at least one of dithia-octane, 4,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithia-undecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithia-undecane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithia-undecane, pentaerythritol tetrathioglycolate, 2,3-dithio(2-mercaptoethyl)-1-propane and 2,3-dimercaptoethylthiopropanethiol.
[0013] As described above, the modified polyurethane polymer optical material, preferably, the acrylate monomer is selected from at least one of methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, hydroxymethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, pentaerythritol tetraacrylate, ethoxylated nonylphenol acrylate, epoxy acrylate, bisphenol A epoxy acrylate and ethoxylated bisphenol A diacrylate.
[0014] On the other hand, the present invention provides a method for preparing the modified polyurethane polymer optical material as described above, the method comprising the following steps:
[0015] (1) adding a polythiol mercaptan compound to a reactor containing a sulfur-containing epoxy compound monomer a, stirring at a speed lower than 95 rpm, and then adding an acrylic ester monomer, an isocyanate and a catalyst respectively, stirring evenly to form a prepolymer;
[0016] (2) The prepolymer is vacuum-defoamed and injected into a tempered mold. The mold containing the prepolymer is placed in a curing oven, heated to 30 to 45° C. for curing for 1 to 3 hours, then heated to 45 to 55° C. for curing for 2 to 5 hours. After naturally cooling to room temperature, the prepolymer is demolded and sampled to obtain a modified polyurethane polymer optical material.
[0017] In the preparation method as described above, preferably, the catalyst is selected from one of stannous octoate, dibutyltin dilaurate, dibutyltin dichloride and dibutyltin oxide.
[0018] In the preparation method as described above, preferably, the amount of the catalyst used is 0.1 to 0.3 wt % of the isocyanate.
[0019] In the preparation method as described above, preferably, the step (1) further comprises adding a light absorber, a colorant, a release agent, an initiator and / or a curing agent.
[0020] In yet another aspect, the present invention provides use of the modified polyurethane polymer optical material as described above as a prism, a lens or a protective screen.
[0021] The sulfur-containing epoxy compound (a) of the present invention can be prepared by the following method: adding epichlorohydrin and trithiomercaptan to a reaction container containing methanol, adding a sodium hydroxide aqueous solution with a concentration of 6-10wt% dropwise with stirring within 10-30 minutes, reacting for 6-10 hours at a temperature of 0-15°C, wherein the weight ratio of epichlorohydrin, trithiomercaptan and methanol is (25-60): (30-70): (100-150), and the amount of sodium hydroxide solution added is 5-10wt% of the content of methanol; continuing to add a 30-40wt% sodium hydroxide aqueous solution dropwise at the same rate, raising the temperature to 25-35°C, stopping the dropwise addition after precipitation occurs, reacting for 1-3 hours, adding chloroform and water to extract the organic layer, eluting and rotary evaporation to obtain a colorless and transparent sulfur-containing epoxy compound monomer (a).
[0022] Beneficial effects of the present invention:
[0023] 1. The present invention uses a sulfur-containing epoxy compound (a) as a monomer for synthesizing a modified polyurethane polymer. The compound has a high visible light transmittance and refractive index. The modified polyurethane composition optical material prepared therefrom has excellent optical properties, high transparency and high transmittance in the visible light and specific wavelength range, and improves the efficiency of the optical system. At the same time, the sulfur-containing epoxy compound (a) can enhance the strength and wear resistance of the polymer, and has a low cost, thereby reducing the overall cost of the polyurethane polymer.
[0024] 2. The modified polyurethane polymer optical material of the present invention is composed of a quaternary crosslinking curing system of polythiothiol compounds, isocyanates, sulfur-containing epoxy compounds, and acrylates. Compared with conventional polyurethane polymer optical materials, the strength and toughness of the material are enhanced, making it have better wear resistance and impact resistance. This enables the optical material to better cope with various complex mechanical environments during use and improves the reliability of optical components.
[0025] 3. The preparation process of the present invention is relatively simple, easy to operate and control, and is conducive to large-scale production. Through reasonable process formula adjustment, the material properties can also be precisely controlled to meet the needs of different optical components. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The transmission spectra of the samples prepared in Preparation Example, Example 1 and Comparative Example 1 are shown.
[0027] Figure 2 The refractive index spectra of the samples prepared in Preparation Example, Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0028] The present invention is further described below by means of specific examples, but this is not intended to limit the protection scope of the present invention.
[0029] Preparation Example: Preparation of sulfur-containing epoxy compound monomer (a)
[0030] 4500g of epichlorohydrin and 5000g of 1,3,5-trimercaptomethylbenzenethiol are added to a reaction container containing 12000g of methanol, and 900g of 9wt% sodium hydroxide solution is added dropwise under stirring for 50 minutes, and the mixture is reacted at 10°C for 6.5 hours. A 36wt% sodium hydroxide aqueous solution is added dropwise at the same rate, and the temperature is raised to 30°C. After 47 minutes, a precipitate appears, and the addition is stopped. The reaction is continued for 1.5 hours, and chloroform and water are added to extract the organic layer. The organic layer is eluted and rotary evaporated to obtain 4625g of a colorless and transparent sulfur-containing epoxy compound monomer (a).
[0031] Example 1: Preparation of modified polyurethane polymer optical material
[0032] 360g of 2,3-dithio (2-mercaptoethyl)-1-propane was added to a reactor containing 450g of sulfur-containing epoxy compound monomer (a), and stirred at a low speed of 90 rpm, and then 120g of pentaerythritol tetraacrylate, 590g of diphenylmethane diisocyanate and 1.5g of dibutyltin dilaurate were added and stirred to form a prepolymer. The prepolymer was vacuum degassed and injected into a tempered mold, and the mold containing the prepolymer was placed in a curing furnace, heated to 40°C for curing for 2h, and then heated to 50°C for curing for 3.5h, and then naturally cooled to room temperature and demolded and sampled to obtain a modified polyurethane polymer optical material.
[0033] Example 2: Preparation of modified polyurethane polymer optical material
[0034] 360 g of 2,3-dithio(2-mercaptoethyl)-1-propane is added to a reactor containing 450 g of a sulfur-containing epoxy compound monomer (a), and the mixture is stirred at a low speed of 90 rpm. Then, 120 g of pentaerythritol tetraacrylate, 700 g of diphenylmethane diisocyanate and 1.5 g of dibutyltin dilaurate are added and stirred to form a prepolymer. The prepolymer is vacuum degassed and injected into a tempered mold. The mold containing the prepolymer is placed in a curing furnace, heated to 40° C. for curing for 2 h, then heated to 50° C. for curing for 3.5 h, and then naturally cooled to room temperature and demolded and sampled to obtain a modified polyurethane polymer optical material.
[0035] Example 3: Preparation of modified polyurethane polymer optical material
[0036] 360 g of 2,3-dithio(2-mercaptoethyl)-1-propane is added to a reaction container containing 280 g of a sulfur-containing epoxy compound monomer (a), and the mixture is stirred at a low speed of 90 rpm. Then, 120 g of pentaerythritol tetraacrylate, 550 g of isophorone diisocyanate and 1.4 g of dibutyltin dilaurate are added and stirred to form a prepolymer. The prepolymer is vacuum degassed and injected into a tempered mold. The mold containing the prepolymer is placed in a curing furnace, heated to 40° C. for curing for 2 h, then heated to 50° C. for curing for 3.5 h, and then naturally cooled to room temperature and demolded and sampled to obtain a modified polyurethane polymer optical material.
[0037] Example 4: Preparation of modified polyurethane polymer optical material
[0038] 360 g of 2,3-dithio(2-mercaptoethyl)-1-propane is added to a reaction container containing 450 g of a sulfur-containing epoxy compound monomer (a), and the mixture is stirred at a low speed of 80 rpm. Then, 120 g of hydroxymethyl methacrylate, 520 g of toluene diisocyanate and 1.2 g of dibutyltin dilaurate are added and stirred to form a prepolymer. The prepolymer is degassed in a vacuum and injected into a tempered mold. The mold containing the prepolymer is placed in a curing furnace, heated to 40° C. for curing for 2 h, then heated to 50° C. for curing for 3.5 h, and then naturally cooled to room temperature and demolded and sampled to obtain a modified polyurethane polymer optical material.
[0039] Example 5: Preparation of modified polyurethane polymer optical material
[0040] 360 g of 2,3-dithio(2-mercaptoethyl)-1-propane is added to a reactor containing 350 g of a sulfur-containing epoxy compound monomer (a), and the mixture is stirred at a low speed of 85 rpm. Then, 120 g of hydroxymethyl methacrylate, 540 g of m-phenylenedimethyl isocyanate and 1.3 g of dibutyltin dilaurate are added and stirred to form a prepolymer. The prepolymer is vacuum-debubbled and injected into a tempered mold. The mold containing the prepolymer is placed in a curing furnace, heated to 40° C. for curing for 2 h, then heated to 50° C. for curing for 3.5 h, and then naturally cooled to room temperature and demolded and sampled to obtain a modified polyurethane polymer optical material.
[0041] Example 6: Preparation of modified polyurethane polymer optical material
[0042] 360 g of 2,3-dithio(2-mercaptoethyl)-1-propane is added to a reactor containing 480 g of a sulfur-containing epoxy compound monomer (a), and the mixture is stirred at a low speed of 90 rpm. Then, 120 g of hydroxymethyl methacrylate, 650 g of m-phenylenedimethyl isocyanate and 1.5 g of dibutyltin dilaurate are added and stirred to form a prepolymer. The prepolymer is vacuum-debubbled and injected into a tempered mold. The mold containing the prepolymer is placed in a curing furnace, heated to 40° C. for curing for 2 h, then heated to 50° C. for curing for 3.5 h, and then naturally cooled to room temperature and demolded and sampled to obtain a modified polyurethane polymer optical material.
[0043] Comparative Examples 1-3:
[0044] Comparative Examples 1-3 respectively adopt the preparation conditions of Example 1, except that some components are reduced. The specific formulas are shown in Table 1.
[0045] Table 1 Comparison of comparative samples prepared under different formulation conditions
[0046] sample Thiol Isocyanate Epoxy Monomer Acrylate Material Cost Comparative Example 1 √ √ / √ Reduce by 1 / 4 Comparative Example 2 √ √ √ / Reduce by 1 / 3 Comparative Example 3 √ √ / / Cost Baseline Example 1 √ √ √ √ Reduce by 1 / 2
[0047] Example 7: Optical performance testing experiment on polyurethane optical materials
[0048] The optical properties of the polyurethane polymer optical materials prepared in the preparation example, examples 1-6 and comparative examples 1-3 were tested respectively. Transmittance is one of the most important properties of optical materials, which is expressed by transmittance. The UV-8000 ultraviolet visible photometer of Shanghai Yuanxi Instrument Co., Ltd. was used for the test. The test method was: directly place the sample on the ultraviolet visible photometer to measure the transmittance; the refractive index test was performed using the WZS1 Abbe refractometer of Shanghai Optical Instrument Equipment Co., Ltd. The test method was: place the polyurethane optical material sample prepared in the example on the prism of the Abbe refractometer to measure the refractive index; the yellow performance test was based on the GB / T 2409-80 standard. The test method was: use a colorimeter to directly read the X, Y, and Z values, and calculate the value by the formula YI = (1.28X-1.06Z) × 100÷Y. The test results are shown in Table 2.
[0049] Table 2 Optical properties of substrate samples prepared under different formulation conditions
[0050] sample Transmittance (T%) Refractive index (Vd) Yellowness Index (YI) Preparation Example 89.3 1.583 1.02 Example 1 89.7 1.643 1.09 Example 2 89.9 1.641 1.07 Example 3 89.3 1.633 1.19 Example 4 89.5 1.645 1.10 Example 5 89.4 1.629 1.12 Example 6 89.8 1.622 1.07 Comparative Example 1 89.3 1.649 1.29 Comparative Example 2 89.6 1.645 1.25 Comparative Example 3 89.1 1.637 1.26
[0051] The data results in Table 2 can be seen:
[0052] 1. Compared with Example 1, Comparative Example 1 does not contain the sulfur-containing epoxy monomer (a), and the yellowness index of the substrate sample increases.
[0053] 2. Compared with Example 1, Comparative Example 2 does not contain acrylate, and the yellowness index of the substrate sample increases.
[0054] 3. Compared with Example 1, Comparative Example 3 does not contain the sulfur-containing epoxy monomer (a) and acrylate, and the yellowness index of the substrate sample increases.
[0055] Conclusion: Combined with the data in Table 1, the product of Example 1 effectively reduces the yellowness index of the material while meeting the requirements of medium and high refractive index optical performance, and reduces the material cost by 1 / 2, thereby improving the product's application range and competitiveness.
[0056] Example 8: Testing the hardness and impact strength of polyurethane polymer optical materials
[0057] The hardness and impact strength performance tests were performed on the polyurethane polymer optical materials prepared in Examples 1-6 and Comparative Examples 1-3. Surface hardness test: The surface hardness of the polymer resin sample is expressed by pencil hardness, referring to the standard GB / T6739-1996. A Chinese high-grade drawing pencil with a core diameter of 1mm and a flattened tip is used. During the test, a force of 1kg is used to push forward along 45°C. The pencil hardness with the maximum hardness without scratches is the surface hardness of the sample. The impact strength meter is the highest steel ball mass with no cracks on the surface of the substrate. For example, a 90g steel ball impacts three times, and the material has no cracks. A 100g steel ball impacts cracks, and the impact strength of this material is 90g. Test method: A substrate with a central thickness of 2.0mm and a certain curvature is fixed at the bottom of the instrument with the convex surface facing up. Steel balls of different masses (80g, 90g, 100g) are selected and vertically and freely dropped from a height of 1.30m to the center of the surface of the substrate material. Each mass of the steel ball is measured three times. The test results are shown in Table 3.
[0058] Table 3 Mechanical properties of substrate samples prepared under different formulation conditions
[0059]
[0060] The data results in Table 3 can be seen:
[0061] 1. Compared with Example 1, Comparative Example 1 does not contain the sulfur-containing epoxy monomer (a), and the surface hardness and impact resistance of the substrate sample are reduced;
[0062] 2. Comparative Example 2 does not contain acrylate compared to Example 1, and the surface hardness and impact resistance of the substrate sample are reduced;
[0063] 3. Compared with Example 1, Comparative Example 3 does not contain the sulfur-containing epoxy monomer (a) and acrylate, and the surface hardness and impact resistance of the substrate sample are reduced.
[0064] Conclusion: The product of Example 1 effectively improves the surface hardness and impact resistance of the material while meeting the mechanical properties of the material.
Claims
1. A modified polyurethane polymer optical material, characterized in that: The material is polymerized from the following components:
2. The modified polyurethane polymer optical material according to claim 1, characterized in that: The isocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, diphenyl ether diisocyanate, triphenylmethane triisocyanate, cyclohexane diisocyanate, 4,4'-diisocyanate dicyclohexylmethane, diethylene diisocyanate, tetramethylene diisocyanate, xylylene diisocyanate, tetramethyl-m-xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dithiodipropyl diisocyanate, dithiodiethyl diisocyanate, trimethylhexamethylene diisocyanate, thiodihexyl diisocyanate, thiodipropyl diisocyanate, lysine triisocyanate, o-tolidine diisocyanate and m-xylylene diisocyanate.
3. The modified polyurethane polymer optical material according to claim 1, characterized in that: The polythiol mercaptan is a compound containing 3 or more thiol functional groups.
4. The modified polyurethane polymer optical material according to claim 3, characterized in that: The polythiothiol mercaptan is selected from the group consisting of methanetrithiol, 1,2,3-trimercaptopropane, 1,1,1-tris(mercaptomethyl)propane, dimercaptomethyl-1,4-dithiacyclohexane, 2-(2,2-bis(mercaptomethylthio)ethyl)-1,3-dithiacyclohexane, 4,6-bis(mercaptomethylthio)1,3-dithiacyclohexane, 4-mercaptomethyl-1,8-dimercapto-3,6-dithia-octane, 4,7- At least one of dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, pentaerythritol tetrathioglycolate, 2,3-dithio(2-mercaptoethyl)-1-propane and 2,3-dimercaptoethylthiopropanethiol.
5. The modified polyurethane polymer optical material according to claim 1, characterized in that: The acrylic acid ester monomer is selected from at least one of methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, hydroxymethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, pentaerythritol tetraacrylate, ethoxylated nonylphenol acrylate, epoxy acrylate, bisphenol A epoxy acrylate and ethoxylated bisphenol A diacrylate.
6. The method for preparing the modified polyurethane polymer optical material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) adding a polythiol mercaptan compound to a reactor containing a sulfur-containing epoxy compound monomer a, stirring at a speed lower than 95 rpm, and then adding an acrylic ester monomer, an isocyanate and a catalyst respectively, stirring evenly to form a prepolymer; (2) The prepolymer is vacuum-defoamed and injected into a tempered mold. The mold containing the prepolymer is placed in a curing oven, heated to 30 to 45° C. for curing for 1 to 3 hours, then heated to 45 to 55° C. for curing for 2 to 5 hours. After naturally cooling to room temperature, the prepolymer is demolded and sampled to obtain a modified polyurethane polymer optical material.
7. The preparation method according to claim 6, characterized in that: The catalyst is selected from one of stannous octoate, dibutyltin dilaurate, dibutyltin dichloride and dibutyltin oxide.
8. The preparation method according to claim 6 or 7, characterized in that: The amount of the catalyst used is 0.1-0.3 wt % of the isocyanate.
9. The preparation method according to claim 6 or 7, characterized in that: The step (1) further comprises adding a light absorber, a colorant, a release agent, an initiator and / or a curing agent.
10. Use of the modified polyurethane polymer optical material according to any one of claims 1 to 5 as a prism, a lens or a protective screen.
Citation Information
Cited By
Preparation method of pentaerythritol tetrathiol carboxylate composition
CN120485298A